Medicare shared savings programs: Higher cost accountable care organizations are more likely to achieve savings. (15th December 2020) - Berkson, Stephanie; Davis, Sarah; Karp, Zaher; Jaffery, Jonathan; Flood, Grace; Pandhi, Nancy
ABSTRACT: In the United States, Medicare's flagship Accountable Care Organization (ACO) program, the Medicare Shared Savings Program (MSSP), is under close scrutiny to improve healthcare quality and decrease costs. First-year measures, released in November 2014, reveal a wide range of financial and quality performance across MSSP participants. In this observational study, we used 2013 results for 220 participating ACOs to assess key characteristics associated with generating savings. ACOs with higher baseline expenditures were significantly more likely to generate savings than lower cost ACOs. Average quality scores for ACOs that successfully reported on quality were not different between organizations that did and did not generate savings. These findings suggest ACOs that had lower utilization prior to program enrollment are less likely to be rewarded in the current program. This has important policy implications for the MSSP's ability to attract and retain efficient ACOs and incent efforts to reduce waste and improve quality.